2009
DOI: 10.1152/ajpheart.01253.2008
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular remodeling with exercise in hypertension

Abstract: .-We investigated how exercise training superimposed on chronic hypertension impacted left ventricular remodeling. Cardiomyocyte hypertrophy, apoptosis, and proliferation in hearts from female spontaneously hypertensive rats (SHRs) were examined. Four-month-old SHR animals were placed into a sedentary group (SHR-SED; n ϭ 18) or a treadmill running group (SHR-TRD, 20 m/min, 1 h/day, 5 days/wk, 12 wk; n ϭ 18). Age-matched, sedentary Wistar Kyoto (WKY) rats were controls (n ϭ 18). Heart weight was greater in SHR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
53
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 46 publications
11
53
0
3
Order By: Relevance
“…Our laboratory has reported whole heart hypertrophy with echocardiography and histomorphometry with exercise training that is dispersed across several walls of the le ventricular myocardium (anterior, posterior, and septal walls). Isolated cardiomyocytes from exercise trained SHR were both longer and wider relative to sedentary controls [25]. Similar �ndings in swim-trained animals have been reported, such that swim training increased le ventricular weight and le ventricular internal diastolic diameter in the spontaneously hypertensive rats [61].…”
Section: Cardiac Remodelingsupporting
confidence: 81%
See 4 more Smart Citations
“…Our laboratory has reported whole heart hypertrophy with echocardiography and histomorphometry with exercise training that is dispersed across several walls of the le ventricular myocardium (anterior, posterior, and septal walls). Isolated cardiomyocytes from exercise trained SHR were both longer and wider relative to sedentary controls [25]. Similar �ndings in swim-trained animals have been reported, such that swim training increased le ventricular weight and le ventricular internal diastolic diameter in the spontaneously hypertensive rats [61].…”
Section: Cardiac Remodelingsupporting
confidence: 81%
“…Several reports have shown that the heart contains resident cardiac stem cells that are capable of generating new cardiac tissue including cardiomyocytes [26][27][28]. We have recently shown that hypertension slightly increases cardiomyocyte proliferation and the number of c-Kit+ cells in hypertensive rodent myocardium [25]. However, hypertension-induced cell death occurs to a greater extent than cell proliferation, perhaps rendering the hypertensive myocardium with lesser number of functional cells relative to normotensive controls.…”
Section: Apoptosis and Proliferationmentioning
confidence: 90%
See 3 more Smart Citations